Placebo effects and racial and ethnic health disparities: an unjust and underexplored connection - Friesen, Phoebe (Journal of medical ethics, 2018)
While a significant body of bioethical literature considers how the placebo effect might introduce a conflict between autonomy and beneficence, the link between justice and the placebo effect has been neglected. Here, we bring together disparate evidence from the field of placebo studies and research on health inequalities related to race and ethnicity, and argue that, collectively, this evidence may provide the basis for an unacknowledged route by which health disparities are exacerbated. This route is constituted by an uneven distribution of placebo effects, resulting from differences in expressions of physician warmth and empathy, as well as support and patient engagement, across racial and ethnic lines. In a discussion of the ethical implications of this connection, we argue that this contribution to health disparities is a source of injustice, consider ways in which these disparities might be ameliorated and suggest that this conclusion is likely to extend to other realms of inequality as well.